Tari Aswamanu - Putriandini, Putu Gita Rahayu; Suteja, I Kt.; Sudarta, I Gusti Putu (Jurnal Ilmiah Wahana Pendidikan, 2023)
The history of the sacred life of the people of Endut Hamlet, West Lombok Regency regarding This phenomenon became the trigger for the creation of a contemporary work entitled Aswamanu Dance. This creation uses the Manujar (human-horse) creation method, namely combining the Manujar (human-horse) creation method, which combines human movement and character with horse (horse) concept, creates the concept of dreams and reality. To analyze image theory and imagination, namely certain images according to the power possessed are implemented into motion motives. The stages are through the method of Creating Through Dance by Y. Sumadiyo Hadi namely; the stages of assessment, experimentation, and formation, as well as the theory of creativity by Nur Iswantara, namely the ability to produce something new. To realize the idea, the surrealist approach is used, which is a visual language that moves away from realism, by making it up or using imagination to reveal one's own visual style. Aswamanu's dance work is to tell the mystery of a human character resembling a horse, supported by nine female dancers, the musical accompaniment of MIDI (Musical Instrument Digital Interface) is performed on the proscenium stage.